An ice inhabiting bdelloid rotifer from North America - Dimattia, Lydia M.; Saglam, Naim; Saunders, Ralph; Shain, Daniel H. (Springer Japan Kk, 2025)
Bdelloid rotifers are major components of zooplankton worldwide and have been reported in glacier ice in both Northern and Southern Hemispheres. Curiously, no reports of psychrophilic bdelloids have surfaced in North America despite exhaustive surveys of other ice-dwelling invertebrates, e.g., glacier ice worms. This distribution gap may be partially explained by a predator-prey relationship between these two animals, but the current study suggests that ice worms and bdelloids can co-inhabit at least some glacial ecosystems over geological time. Here we report the first ice-inhabiting bdelloid rotifer from North America, collected from the northern aspect of Mt. Deception, WA, USA. Nuclear and mitochondrial genotyping identified sister-species relationships within a clade of Nordic ice-dwelling bdelloids, and close evolutionary relationships with Antarctic/New Zealand specimens. Intrapopulation genetic divergences suggest that bdelloids arrived in North America near the onset of the Pleistocene (2.58 myr BP), but their circumpolar dispersal capabilities and robustness (e.g., freeze-thaw tolerance, ability to propagate at elevated temperatures and under extreme laboratory conditions) cannot rule out multiple transoceanic dispersal events throughout the Quaternary.
Keywords: Glacier; Pleistocene; Pacific Northwest; Psychrophile; Cold adaptation; Metagenomics; Intraguild predation